Anaesthetics modulate tumour necrosis factor α: effects of L-carnitine supplementation in surgical patients. Preliminary results. - Giovanna Delogu; Claudio De Simone; Giuseppe Famularo; Alessandra Fegiz; Francesca Paoletti; Emilio Jirillo (Hindawi Limited, 1993)
Both anaesthetics and surgical trauma could strongly affect the production of tumour necrosis factor α (TNFα). During in vitro experiments the authors found that anaesthetics modulate the production of TNFα by peripheral blood mononuclear cells. Notably, Pentothal strongly increased the production of the cytokine as compared to both lipopolysacchride treated and control mononuclear cells, whereas in supernatants from Leptofen driven mononuclear cells TNFα was strongly reduced. On the other hand, Pavulon did not significantly affect the cytokine production. In the in vivo study, in an attempt to ameliorate the metabolic response to surgical trauma, L-carnitine was administered to 20 surgical patients, then the circulating TNFα was measured. The results indicate that the levels of circulating TNFα were strongly increased following surgery and that L-carnitine administration resulted in a strong reduction of TNFα. Thus, the data suggest that L-carnitine could be helpful in protecting surgical patients against dysmetabolism dependent on dysregulated production of TNFα.